BENTUK PERKAWINAN HUKUM ADAT MANDAILING - Harahap, Herlina Hanum; Lubis, Muhammad Ridwan; Manurung, Dormauli (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2024)
Adat in the madailing tribe involves many people from dalian na tolu, such as mora, kahanggi and anak boru. The wedding ceremony procession starts with customary deliberation called makkobar or markkatai, which is talking in a very special and unique way. speech that is very special and unique. Each member exchanges speeches, such as taking turns replying to rhymes. The first person to open the conversation is the spokesperson who has a hajat (suhut), followed by the son-in-law who has a hajat (anak boru suhut). son-in-law (anak boru suhut), the brother-in-law of the son boru (pisang raut), the participants of the deliberation who are present (paralok raut). who are also present (paralok-alok), the traditional king of the village (hatobangan), the customary king of the neighboring village (raja torbing balok) and the raja of the diraja adat or the presiding officer (raja panusunan bulang). Keywords: Marriage, Custom, Mandailing. Batak, Toba